Respostas

2014-06-25T12:54:24-03:00
A) (2x+2y).(2x+2y) = 4x²+4xy+4xy+4y² = 4x²+8xy+4y² / b)(4+2y).(4+2y) = 16+8y+8y+4y² = 16+16y+4y² / c) (2x+a).(2x+a) = 4x²+2ax+2ax+a² = 4x²+4ax+a² / d) (3a+5).(3a+5) = 9a²+15a+15a+25 = 9a²+30a+25

e)(7x-2y).(7x-2y) = 49x²-14xy-14xy+4y² = 49x²-28xy+4y² / f) ((2x-2y).(2x-2y) = 4x²-4xy-4xy+4y² = 4x²-8xy+4y² / g) (6b+2a).(6b+2a) = 36b²+12ab+12ab+4a² = 36b²+24ab+4a² / h) (√9x+y). (√9x+y) = √81x²+√9xy+√9xy+y² = 9x+2√9xy+y² / i) (2x+√4). (2x+√4) = 4x²+2x√4+2x√4+√16 = 4x²+4x√4+4 / j) (8+4/3x). (8+4/3x) = 64+32/3x+32/3x+16/9x² = 64+64/3x+16/9x² /
(3x-5/2y)+ (3x-5/2y)= 9x²-15/2xy-15/2xy+25/4y² = 9x²-30/2xy+25y²
l) 0²+0+0+0@ = 0
obrigada